Pengaruh dari Social Media Marketing Activity, Customer Experience dan Product Quality dalam Memengaruhi Repurchase Intention pada Produk Erigo - Kevin Alifka Damaputra (Universitas 45 Surabaya, 2023)
Social media marketing activities are important for companies to market their products in this digital age, where they can help companies continue to compete in the market. Therefore, this study aims to determine the size of the influence of social media marketing activities, customer experience, product quality on repurchase intentions. The population in this study were people who had bought Erigo products once or more in the Jakarta and Tangerang areas. This research is a quantitative study using primary data as well as data collection techniques carried out in this study, namely using questionnaires distributed questionnaires using a Likert scale of 1-5 and distributed to 140 respondents. The analytical tool used in this study is multiple linear regression. The findings in this study show that social media marketing activity, customer experience, and product quality have a significant effect on repurchase intention. Then, this study has limitations, namely the number of samples that are still not large enough to describe the actual situation.